Pengaruh Kompetensi Sumber Daya Manusia Terhadap Tingkat Loyalitas Nasabah - Rahmawati Akeda; Harun Masykur; Regita Cahyani (Prodi Perbankan Syariah FAI UMT, 2020)
This research aims to data This research aims to determine whether the influence of human resources competence on the level of customer loyalty in the BPRS Harta Insan Karimah branch Karawaci. This type of research is field research with a quantitative approach with 40 respondents. Data that is used is the result of the processing of answers respondents to the questionnaire that was shared by researchers to customers of PT. BPRS Harta Insan Karimah branch Karawaci. The results of this study concluded that the competency of human resources has a positive effect on the level of customer loyalty, as the test result obtained by t Account of 4.886 is greater than the This IE 2.024 (4.886 > 2.024). Based on the test T shows a significant result of 0.000 < 0.05 which means that human resource competence significantly affects the level of customer loyalty. Based on the results the correlation coefficient indicates a strong and positive relationship between the two variables and the result of the coefficient of determination can be known that independent variables describe the dependent variable by 38.6%.